Development and first application of the athlete adaptation inventory: An exploratory study - Ryba, T. V.; Elbe, A.-M.; Darpatova-Hruzewiczc, D. (Performance Enhancement & Health, 2020)
Geographic mobility has become an essential part of athletes` career development and athletic migration is rapidly increasing. However, research on psychological aspects of athletes` transnational mobility is lacking in the literature. In this study we describe the development of the Athlete Adaptation Inventory (AAI) and examine its first application in a sample of 143 professional and amateur elite migrant athletes. In summary, results indicate that cultural adaptation challenges were perceived as slightly difficult. However, female athletes reported more difficulties than male athletes in the sport domain, whereas male and team sport athletes reported more challenges in the non-sport domain compared to female and individual sport athletes. Furthermore, difficulties encountered in everyday activities of the target destination significantly predicted challenges adapting to the sport environment, whereas gender contributed to a much lesser degree. To explore diverse ways in which cultural transitions are experienced and to provide adequate support, sport practitioners are encouraged to include this scale in their work with migrating athletes.